2011
DOI: 10.1007/s00167-011-1612-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of medial meniscus injury and meniscectomy on the variability of gait parameters

Abstract: The complexity of gait decreased if the walking speed differed from the self-selected speed. Prior to and after meniscectomy, the decreased variability of angular parameters on the affected side of patients represented decreased flexibility of joints. This led to decreased consistency in movements of the lower limbs from stride to stride, as shown by the increased variability of spatial-temporal parameters. A decrease in joint flexibility and consistency of movement can be associated with a decreased complexit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
1
13
0
2
Order By: Relevance
“…Palm et al (2010) did not report the location and degree of meniscus injury; thus, those patients may have had both medial and lateral meniscus injuries. This result was also consistent with the conclusions previously drawn from gait analysis (Bulgheroni et al, 2007) and gait variability (Magyar et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Palm et al (2010) did not report the location and degree of meniscus injury; thus, those patients may have had both medial and lateral meniscus injuries. This result was also consistent with the conclusions previously drawn from gait analysis (Bulgheroni et al, 2007) and gait variability (Magyar et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…On the basis of our results it can be assumed that the one-year postoperative period was not enough for the regeneration of mechanoreceptors in the meniscus. Previous research demonstrated differences in gait parameters (Bulgheroni et al, 2007;Magyar et al, 2008) and in the variability of gait (Magyar et al, 2011). Postural stability and joint positioning were defective postoperatively compared to controls (Jerosh et al, 1996;Al-Dadah et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many researchers pointed out that the secondary injuries, e.g., cartilage injury, meniscus injury, and KOA, can occur if not treated in time. And the ligament reconstruction, as a recognized effective treatment, can dramatically recover the knee biomechanics [85][86][87][88]. In the five types of injures, nearly half of ligament injuries are isolated injuries to the ACL [89].…”
Section: Knee Musculoskeletal Disorders and Its Biomechanicalmentioning
confidence: 99%
“…Также выявлены отличия в фазовой активности мышц и соответствующие компенсаторные изменения на здоровой стороне. В другом исследовании этих же авторов показано, что снижается произвольная скорость ходьбы, уменьшается адаптивность движений суставов на стороне поражения, уменьшается сложность движения в целом [18]. d.l.…”
unclassified